High temperature resistance of desert sand concrete: Strength change and intrinsic mechanism. (11th April 2022) - Shen, Yanjun; Peng, Cheng; Hao, Jianshuai; Bai, Zhipeng; Li, Yugen; Yang, Bohan
Highlights: The strength and workability are the best when the replacement rate of desert sand is 20% and 40% at high temperature. The influence mechanism of desert sand on high temperature resistance of concrete is revealed. The difference of high temperature resistance between ordinary concrete and desert sand concrete under different high temperature conditions is discussed and analyzed. The influence of desert sand on the high temperature resistance of concrete is mainly reflected in its physical and chemical properties. Abstract: Desert Sand Concrete (DSC) is gradually being better applied in the construction process of energy bases in the nearby areas of Chinese deserts, where the high temperature resistance is an important link to evaluate its application effect. In this paper, the strength change, microstructure and chemical composition change of DSC under high temperature environment are analyzed. Through systematic tests such as uniaxial compression test, NMR, XRD, SEM and EDS, we mastered the influence of high temperature and desert sand replacement rate (DSRR) on the strength of DSC, and revealed the internal mechanism of strength change of DSC under high temperature conditions. The research conclusions are as follows: (1) the compressive strength of DSC experienced a process of "increase first and then decrease" with the rise of temperature, and the room temperature ∼400 °C is the upward stage. This is due to the fact that the early temperature rise promotes the hydration reaction, and the hydration products improve and enhance the ITZ and pore structure compactness. (2) The compressive strength growth of DSC between room temperature and 400 °C at DSRR of 20% and 40% is greater than that of ordinary concrete (OC). Compared with OC, the growth rate of compressive strength after high temperature treatment at 400 °C is 12% and 16.1%, which is higher than that at room temperature (10.5% and 7.7%). (3) The appropriate amount of desert sand can effectively reduce the porosity. Compared with OC, when DSRR is 20% and 40%, the porosity of DSC at room temperature ∼400 °C decreases by 73.7% and 34.8% respectively. (4) The mechanism of the intrinsic influence of DSRR on the characteristics of DSC strength change under high temperature conditions is as follows: Compared with OC, DSC with DSRR of 20% and 40% produces more cementitious products such as C-S-H with low alkalinity and stable morphology internally, which can effectively improve the pore structure and aggregate - mortar interfacial cementation performance and better high temperature resistance. This study has a guiding value for the study of high temperature resistance of DSC and potential engineering applications.